Implementing a blockchain-based local energy market: Insights on communication and scalability - Meeuw, Arne; Schopfer, Sandro; Wörner, Anselma; Ableitner, Liliane; Tiefenbeck, Verena; Fleisch, Elgar; Wortmann, Felix (Computer Communications, 2020)
Peer-to-peer (P2P) energy markets are gaining interest in the energy sector as a means to increase the share of decentralised energy resources (DER), thus fostering a clean, resilient and decentralised supply of energy. Various reports have touted P2P energy markets as ideal use case for blockchain-technology, as it offers advantages such as fault-tolerant operation, trust delegation, immutability, transparency, resilience, and automation. However, relatively little is known about the influence of hardware and communication infrastructure limitations on blockchain systems in real-life applications. In this article, we demonstrate the implementation of a real-world blockchain managed microgrid in Walenstadt, Switzerland. The 37 participating households are equipped with 75 special smart-metres that include single board computers (SBC) that run their own, application-specific private blockchain. Using the field-test setup, we provide an empirical evaluation of the feasibility of a Byzantine fault tolerant blockchain system. Furthermore, we artificially throttle bandwidth between nodes to simulate how the bandwidth of communication infrastructure impacts its performance. We find that communication networks with a bandwidth smaller than 1000 kbit/s – which includes WPAN, LoRa, narrowband IoT, and narrowband PLC – lead to insufficient throughput of the operation of a blockchain-managed microgrid. While larger numbers of validators may provide higher decentralisation and fault-tolerant operation, they considerably reduce throughput. The results from the field-test in the Walenstadt microgrid show that the blockchain running on the smart-metre SBCs can provide a maximum throughput of 10 transactions per second. The blockchain throughput halts almost entirely if the system is run by more than 40 validators. Based on the field test, we provide simplified guidelines for utilities or grid operators interested in implementing local P2P markets based on BFT systems.<br
Keywords: Local energy markets; Peer-to-peer trading; Blockchain managed microgrid; Smart grid communication; Network requirements